Clinical Expression of an Inherited Unbalanced Translocation in Chromosome 6. (25th September 2011) - Ganguly, Bani Bandana; Kadam, Vijay; Kadam, Nitin N.
Abstract : Unbalanced chromosomal rearrangements are not common; however, they have a significant clinical expression. The parental balanced translocation produces unbalanced chromosome, which is transmitted to next generation through fertilization of gametes carrying the derivative chromosome. The carriers of balanced rearrangements mostly do not have recognizable phenotypic expression. We report a family comprising of healthy and non-consanguineous young parents and their preemie newborn severely affected with congenital anomalies and systemic disorders. Conventional Gbanding analysis of somatic chromosomes identified a balanced translocation, t(6;10)(p23;q24), in mother and an unbalanced rearrangement, der(6)t(6:10)(p23;q24)mat, in the child. The child has inherited a derivative chromosome 6 with partial deletion of 6(p23-pter) and partial trisomy 10(q24-qter), which has resulted in fusion of genes of two different chromosomes. The prominent phenotypic features of del(6p), including high forehead, flat nasal bridge, agenesis of left ear, atrial septal defect (ASD), craniosynostosis, and growth retardation, are overlapping with specific Axenfeld-Reiger-, Larsen-, and Ritscher-Sinzel/3-C syndromes, however, lacking in ocular anomalies, skeletal laxity, or cerebellar malformation. Therefore, this paper rules out the isolated effect of del(6p23) or trisomy 10(q24) on distinct previously reported syndromes and proposes the combined effect of unbalanced chromosomal alteration.